Analysis on the Quality of Epimedii Folium Originating From Cultivated Epimedium Pubescens Maxim (Bangladesh Journal of Botany, 2021)
The contents of main medicinal componentsin cultivated Epimedii foliumand yield plant originating fromEpimediumpubescensMaxim were compared to evaluate the quality of cultivated Epimedii folium.The concentration of icariin and epimedin C in the extracts came from cultivated E.pubescens and yield one were, respectively determined with RP-HPLC. The results showed that the contents of main medicinal componentsin cultivated E.pubescens were all lower than that in yield of E.pubescens. The quality of cultivated Epimedii folium is inferior to that of yield one. The cultivated E. brevicornumaterials can be used as medicinal materials because there are considerable medicinal chemical components in cultivated E.pubescens.Bangladesh J. Bot. 50(2): 295-299, 2021 (June)